Corruption in Commercial Transactions - Pulle, Austin Ignatius (Institutional Knowledge at Singapore Management University, 2010)
Aristotle asked how one should live one's life. This question is more relevant to us today than it was several millennia ago because the decisions of leaders and other people can have widespread effects not only on the jobs, health and wealth of billions of human beings, but also on the environment. Every major decision made in business, government and society is fundamentally an ethical one with widespread social responsibility implications. Whether it is the global sale of worthless financial derivatives, the adulteration of milk and infant formula with toxic material or the abuse of technology leading to invasion of privacy, the disregard of ethical principles has resulted in the degradation of the quality of life and dehumanization of the individual. Written by seven faculty members of the School of Law at the Singapore Management University (SMU), Ethics and Social Responsibility draws upon the scholarship and history of the West and also presents lessons, examples and situations that are relevant to Asia. Originally conceived as a textbook for SMU students reading Ethics and Social Responsibility as a university core curriculum course, the book balances judiciously between theory and practice to allow readers to apply their theoretical understanding of concepts to real-world scenarios. In addition, open-ended questions are included to provoke deeper reflection and discussion, while illustrations and case studies highlight ethical concepts and their applications. The writers expertly capture the sense of dynamism of ethics and social responsibility and sensitize readers to deal with these issues in the real world.